Community Perceptions of the Progo River Sand and Stone Mining Activities in Yogyakarta (Study in the Communities of Sendangagung Village, Minggir, Sleman Yogyakarta) - Djaja, Sylvia Indah; Sujatmika, Sujatmika; Kusharyanti, Kusharyanti (AIBPM Publisher, 2023)
This research aims to determine the perceptions of people living in mining areas regarding the impacts of sand and stone mining activities on the Progo River, Yogyakarta. This research uses a qualitative type with a case study method. Primary data collection was carried out by interviews as well as observations and supporting documents or literature for secondary data. Sand and stone mining activities in the Progo River using heavy equipment by individuals and companies under the pretext of normalizing river flow after the eruption of Mount Merapi based on Decree Number 284 of 2011. This regulation has been misunderstood by various parties, which has given rise to uncontrolled sand mining. One example of mining that caused community rejection occurred in Sendangagung Village, especially the Jomboran, Pundak Wetan and Wiyu areas of Yogyakarta. Researchers found that the community rejected mining because the community had the perception that mining companies took it with heavy equipment without paying attention to the preservation of the land and the environment, which resulted in land degradation, landslides, air pollution and water pollution. Apart from that, the community questions the legitimacy of the government in issuing non-transparent mining permits.